Analysis The Effect of Leadership, Compensation and Motivation on Teacher Performance with Job Satisfaction as an Intervening Variable (Study at Muhammadiyah School Pangandaran District) - Dedi Irama; Amir; Sri Wahyuni; Ahmad Darmawan (South Sulawesi Education Development (SSED), 2024)
This study aims to test independent variables consisting of leadership, compensation and motivation against the dependent variable, namely teacher performance with job satisfaction as an intervening variable. The research approach used is quantitative with the SEM PLS 3 method. The data collection method uses questionnaire distribution techniques and Sample selection in this study uses saturated sampling or census, that is, the population number can be sampled in this study, the sample used as many as 84 respondents displayed results (H1) Rejected there was no significant influence of leadership on teacher performance with a coeficient path (-0.418). (H2) Rejected had no significant effect of compensation on teacher performance with path coeficient (0.156). (H3) Rejected no significant effect of motivation on teacher performance with path coeficient (-0.087). (H4) Rejected had no significant effect of leadership on job satisfaction with path coeficient (0.204). (H5) It is accepted that there is a significant influence of leadership on job satisfaction with a path coeficient (0.496). (H6) Rejected had no significant effect of compensation on job satisfaction with path coeficient (0.136). (H7) Accepted there is a significant effect of motivation on job satisfaction with path coeficient (0.2388). (H8) Rejected that there was no significant effect on the variable of job satisfaction as a mediation between leadership and teacher performance with path coeficient (-0.101). (H9) Rejected there was no significant effect of job satisfaction as a mediation between compensation and teacher performance with path coeficient (-0.028), (H10) Rejected no significant effect of job satisfaction as mediation between motivation and teacher performance with path coeficient (-0.049). The implications for the results of this study show unhealthy organizational processes and environments. So improving management that pays attention to good management is a way to improve human resource management in educational institutions in Muhammadiyah. Keywords: Leadership, Compensation, Motivation, Perfomance, Satisfaction